An extended car-following model considering vehicular gap fluctuation. (June 2015) - Yu, Shaowei; Shi, Zhongke
Abstract: To explore and evaluate the effects of vehicular gap fluctuation on roadway traffic mobility, fuel economy and exhaust emissions, we first analyzed the linkage between vehicular gap fluctuation and the following car's acceleration or deceleration with the measured car-following data, and then developed an extended car-following model considering vehicular gap fluctuation based on the full velocity difference model. Finally, numerical simulations are conducted to explore how vehicular gap fluctuation affects car's velocity, acceleration, vehicular gap, fuel consumptions and exhaust emissions. The results show that vehicular gap fluctuation has significant effects on the dynamic characteristics, fuel consumptions and exhaust emissions of traffic flow, and that considering vehicular gap fluctuation in modeling traffic flow system can improve the stability of traffic flow, increase fuel efficiency and reduce exhaust emissions.